Exonic single nucleotide polymorphisms within TLR3 associated with infant responses to serogroup C meningococcal conjugate vaccine. - O'Connor, D; Moore, C; Snape, M; John, T; Hill, A; Pollard, A (2014)
The introduction of the serogroup C meningococcal (MenC) conjugate vaccination has successfully controlled the burden of disease associated with this serogroup in many countries. However, considerable inter-individual variation is observed in immune responses to MenC vaccine, and little is understood of the determinants of this variability. Previously, we reported an association between single nucleotide polymorphisms (SNPs) in TLR3 and CD44 and the persistence of MenC vaccine immunity. Here we further examine polymorphisms within these two candidate genes and immune responses to MenC vaccine. MenC-specific IgG concentrations and serum bactericidal assay (SBA) titres were measured one month after a primary course of MenC vaccination in 318 human infants. Tagging SNPs (TagSNPs) within TLR3 and CD44 were genotyped and regional imputations carried out to screen these genes for variations associated with immunological responses to MenC vaccine. This study reports an association between an exonic variant (rs3775290, P=0.025) in TLR3 and MenC IgG concentrations, as well as an association between three SNPs in CD44 (rs3794109, P=0.021; rs3794110, P=0.022; rs112762, P=0.049) and MenC SBA titres. These data support our previous findings of an association between SNPs in TLR3 and CD44, and present novel findings implicating exonic variants in these genes with MenC vaccine responses.